Oberg’s Stages of Culture Shock in the Adaptation Process of French Volunteers in Indonesia - Moch Yusuf Alif Permana; Aisyiah Al Adawiyah (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2026)
With increased mobility in the globalization era, more people are moving to other places. The primary objective is to seek novel intercultural experiences and challenges, as is the case with the experience of the French volunteers in Indonesia. Given that Indonesia is recognized for its collectivist culture and France for its individualistic culture, cultural differences are inevitable. According to the questionnaire data, the volunteers reported experiencing culture shock due to the host family’s regulations and the neighborhood’s social norms. Therefore, research on culture shock is needed to determine the four stages of Oberg’s culture shock that volunteers undergo: the honeymoon, crisis, recovery, and acceptance phases. Six volunteers who worked with Dejavato and Civic Service to teach French language and culture were the subject of this quantitative descriptive study. According to Oberg’s theory, the respondents did not experience the crisis phase, as indicated by the findings. The overall results were not significantly impacted by the variety of responses, particularly in topics such as shopping, transportation, and language. Additionally, most volunteers have shown good adaptability to the social environment and Indonesian culture throughout ongoing interactions. The findings indicate that interactions with the local society can support volunteers’ understanding of Indonesian cultural values. This research also found that volunteers can adapt to a new cultural environment effectively.